Medical Toxicology - Erkekoglu, Pınar; Ogawa, Tomohisa (IntechOpen, 2021)
Medical toxicology is a sub-branch of toxicology concerned with the diagnosis, management, and prevention of poisoning and other adverse effects of drugs, cosmetics, personal care products, occupational and environmental toxicants, and biological agents. Poisoning with drugs, herbs, venoms, and toxins is a significant global public health problem. Medical toxicologists are involved in the assessment and treatment of acute or chronic poisoning, substance abuse, adverse drug reactions, drug overdoses, envenomation, industrial accidents, and other chemical exposures. As such, there is a pressing need for safe and specific antidotes, as many antidotes currently in use have a relatively low margin of safety or therapeutic index. This book focuses on poisonings with drugs, venoms, toxins, interaction in clinics, antidotes, and forensics. It provides qualified scientific knowledge on different aspects of medical toxicology, drug and substance abuse, clinical interactions between drugs and herbs, antidotes, antidote networks, and forensic toxicology.